2013
DOI: 10.1002/hup.2373
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of obsessive–compulsive disorder and substance use disorder: a new heuristic

Abstract: Obsessive-compulsive disorder (OCD) and substance use disorder share several aspects of phenomenology and may be underpinned by a common mechanism with compulsivity at the core. Despite this overlap, the two disorders show a variable pattern of comorbidity. Here, we review the current evidence for comorbidity across clinical and epidemiological studies, and propose a new heuristic for substance use comorbidity in OCD, based on a hypothetical threshold of OCD severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Cognitive control reflects a set of processes that serve goal-directed behavior by selecting goals, inhibiting responses and monitoring performance (NIMH, 2017). The perception by experts that impaired response selection inhibition/suppression characterizes OCRDs despite mixed evidence in the literature (Abramovitch and Cooperman, 2015), might have been influenced by impulsive-compulsive models (Fontenelle et al, 2011), which explain why compulsive and impulsive disorders/traits are commonly comorbid, both in clinical (Fontenelle et al, 2005) and in non-clinical (Cuzen et al, 2014) settings. Indeed, recent studies suggest that impulsive and compulsive traits share a common underlying psychopathological structure (Tiego et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive control reflects a set of processes that serve goal-directed behavior by selecting goals, inhibiting responses and monitoring performance (NIMH, 2017). The perception by experts that impaired response selection inhibition/suppression characterizes OCRDs despite mixed evidence in the literature (Abramovitch and Cooperman, 2015), might have been influenced by impulsive-compulsive models (Fontenelle et al, 2011), which explain why compulsive and impulsive disorders/traits are commonly comorbid, both in clinical (Fontenelle et al, 2005) and in non-clinical (Cuzen et al, 2014) settings. Indeed, recent studies suggest that impulsive and compulsive traits share a common underlying psychopathological structure (Tiego et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with clinical samples [10][11][12][13][14] have reported SUD prevalence similar to that of the general population. Other studies [15][16][17] have even suggested that people with OCD might be less likely to use substances owing to risk aversion. In contrast, epidemiological surveys [18][19][20][21][22] have found an elevated risk of SUDs in individuals with OCD.…”
Section: Introductionmentioning
confidence: 99%
“…substance use, trichotillomania and physical aggression) and compulsive behaviours (e.g. grooming, shopping, hoarding or collecting) (Cuzen et al, 2014; Guo et al, 2017). Given comorbidity, overlapping neurocircuitry across OCRDs (Fineberg et al, 2017) and evidence of reactivity to lifestyle factors (Brierley et al, 2021a), it may be the case that there are similar lifestyle factors associated with obsessive-compulsive symptoms (OCS) and other PRBs.…”
Section: Introductionmentioning
confidence: 99%